2019
DOI: 10.1002/adma.201807686
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Butterfly Scale Surfaces with Compliance‐Tailored Anisotropic Drop Adhesion

Abstract: Many natural surfaces such as butterfly wings, beetles' backs, and rice leaves exhibit anisotropic liquid adhesion; this is of fundamental interest and is important to applications including selfcleaning surfaces, microfluidics, and phase change energy conversion. Researchers have sought to mimic the anisotropic adhesion of butterfly wings using rigid surface textures, though natural butterfly scales are sufficiently compliant to be deflected by capillary forces exerted by drops. Here, inspired by the flexible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 39 publications
1
45
0
1
Order By: Relevance
“…CNT, carbon nanotube; CVD, chemical vapor deposition; RIE, reactive ion etching; PS, polystyrene; Si, silicon to many researchers because of their high electroconductivity and lightweight advantages. 7,[34][35][36][37][38] As shown in Figure 5(C), hexagonally arranged microhole arrays were first prepared by photolithography that patterns positive tone PR resist by developing it with solvents. 34 Then, PVD was introduced to deposit catalyst, Fe/Al 2 O 3 , on the PR master mold.…”
Section: Top-down Lithography and Bottom-up Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…CNT, carbon nanotube; CVD, chemical vapor deposition; RIE, reactive ion etching; PS, polystyrene; Si, silicon to many researchers because of their high electroconductivity and lightweight advantages. 7,[34][35][36][37][38] As shown in Figure 5(C), hexagonally arranged microhole arrays were first prepared by photolithography that patterns positive tone PR resist by developing it with solvents. 34 Then, PVD was introduced to deposit catalyst, Fe/Al 2 O 3 , on the PR master mold.…”
Section: Top-down Lithography and Bottom-up Growthmentioning
confidence: 99%
“…Hart et al suggested an approach to modulate the growth rate of the CNTs 7,35,36 to design a freeform morphology of microstructures with a patterned underlayer (Figure 5(E)). 35 A titanium nitride (TiN) layer was selectively deposited on a SiO 2 layer by lithography including a lift-off process.…”
Section: Top-down Lithography and Bottom-up Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Hierarchically patterned surfaces are widely found in natural and man‐made materials and biological skins, in which structures with a topographic hierarchy across multiple scales can impart intriguing and outstanding properties to the surface due to the synergistic effects of hierarchical structures . Inspired by these hierarchical patterns, researchers have engineered hierarchical surfaces for various applications ranging from wetting control and structural colors to tissue scaffolds using diverse patterning approaches, including typical lithography, chemical deposition, and nanoimprinting .…”
mentioning
confidence: 99%